Some Theorems and Results on Solution of Kind of Volterra Integral Equations - Muayyad Khalil (College of Education for Pure Sciences, 2020)
We studied in this work a class of nonlinear Volterra integral equations with delay and present a sufficient condition for the bounded solution also we give an illustrative example which support the main result of this paper.